Design of an L-band phased-array radar - Tan, Liong Hai. (2009)
The systems level design of a proposed L-band phased-array radar is described in this thesis. This radar shall be operated on tactical grounds. Targets are assumed to be high-speed, high-maneuvering air attacks, as such high survivable features of the radar are required. The radar system shall be mounted on a mobile vehicle, easily transported from one site to another. In addition to being mobile, the radar improves survivability in another manner. Besides the antenna, the rest of the radar subsystems are housed in an armored shelter mounted on the truck. This project is focused on the systems level analysis and design aspects of the radar. Detailed designs of the antenna, transmitter, receiver, computer/software and display subsystems are undertaken by other investigators of the research team.